Mythic Religious Naturalism - Rottschaefer, William A. (Zygon, 2007)
Abstract. In his book Religion Is Not About God, Loyal Rue presents an evolutionarily based explanation of religion as a means to further the personal and social fulfillment of human beings. Rue argues that religions in the form of myths, adaptive falsities, provide an account of the connection between what is (facts) and what matters (values). Myths are false because they attribute subjectively based values to valueless facts, but adaptive because they motivate personally and socially beneficial actions. He maintains that the current crises of humankind, evidenced by both social conflict and environmental degradation, indicate that the major religious traditions—all of which project values onto some transcendent reality—are failing to serve humanity. To overcome these crises, Rue maintains that we need a new, scientifically based naturalized religion, one that attributes subjectively based values to Nature instead of a transcendent reality. I accept Rue's naturalism about values but reject his subjectivist account of them. Contrary to Rue, I show that the naturalistic fallacy sets no barrier to the existence of objective moral values. Modeling my view on the selection theories used in biology and psychology, I offer a scientifically based explanation of the origin and existence of objective values and support it with empirical findings from developmental psychology. Whether this account can count as religious, I do not address.